PENGARUH INDEPENDENSI, KOMPETENSI, SKEPTISME PROFESIONAL DAN PROFESIONALISME TERHADAP KEMAMPUAN MENDETEKSI KECURANGAN (FRAUD) PADA AUDITOR DI BPK RI PERWAKILAN PROVINSI SUMATERA UTARA - Sartika Simanjuntak; Amir Hasan; Al Azhar Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the effect of Independency, Competency, Profes-sional Skepticism and Professionalism against Ability to Detect Fraud. The population in this study is auditor who works in Badan Pemeriksa Keuangan Republik Indonesia (The Indonesia’s Supreme Audit Institution) of Sumatera Utara. The sampling technique using survey method. The data of this research using primary data using questionnairs and directly through on BPK-RI of the North Sumatera Province. Through this method, were 60 questionnairs and analyzed using SPSS 17 version. The data were analyzed to test the hypothesis using multiple linear regression analsys approach. The result of this study showed that Competency, Professional Skepticism and Professionalism has effect on Ability to Detect Fraud. While independency has no effect regarding on Ability to Detect Fraud. Determinate Koefisien value is equal to 0.612 which means that 61.2% of the independent variables in this study were able to influence the dependent variable, while the remaining 31.8% is explained by other variables not included in this study.Keywords: Independency, competency, professional skepticism, and fraud